Depressed and swiping my problems for later: the moderation effect between procrastination and depressive symptomatology on internet addiction - Hernández, Cristóbal; Rivera Ottenberger, Diana; Moessner, Markus; Crosby, Ross D.; Ditzen, Beate (Computers in human behavior, 2019)
Based on insights from the model of compensatory internet use and emotion regulation theory, this study aimed to explore two possible mechanisms explaining the reliable association between depressive symptomatology and internet addiction: procrastination on the internet and flow experiences online. Data were collected from 529 high school students, with a mean age of 15.2 years (SD=1.30), enrolled in six schools in a metropolitan region of Chile. Voluntary participants completed self-reported measures of internet addiction, depressive symptomatology, procrastination on the internet, and flow experiences online. A three-level hierarchical linear model was calculated to evaluate the potential moderator effect of flow and procrastination on the relationship between depressive symptomatology and internet addiction. Results revealed that procrastination moderated this relationship while flow experiences online did not. The findings are discussed in terms of their implications for research and clinical practice, highlighting the importance of considering the intentions behind internet usage.
Gesehen am 04.07.2019